Ultrathin Gallium Nitride Quantum-Disk-in-Nanowire-Enabled Reconfigurable Bioinspired Sensor for High-Accuracy Human Action Recognition - Gao, Zhixiang; Ju, Xin; Yu, Huabin; Chen, Wei; Liu, Xin; Luo, Yuanmin; Kang, Yang; Luo, Dongyang; Yao, JiKai; Gu, Wengang; Memon, Muhammad Hunain; Yan, Yong; et al. (Nano-Micro Letters, 2025)
Human action recognition (HAR) is crucial for the development of efficient computer vision, where bioinspired neuromorphic perception visual systems have emerged as a vital solution to address transmission bottlenecks across sensor-processor interfaces. However, the absence of interactions among versatile biomimicking functionalities within a single device, which was developed for specific vision tasks, restricts the computational capacity, practicality, and scalability of in-sensor vision computing. Here, we propose a bioinspired vision sensor composed of a GaN/AlN-based ultrathin quantum-disks-in-nanowires (QD-NWs) array to mimic not only Parvo cells for high-contrast vision and Magno cells for dynamic vision in the human retina but also the synergistic activity between the two cells for in-sensor vision computing. By simply tuning the applied bias voltage on each QD-NW-array-based pixel, we achieve two biosimilar photoresponse characteristics with slow and fast reactions to light stimuli that enhance the in-sensor image quality and HAR efficiency, respectively. Strikingly, the interplay and synergistic interaction of the two photoresponse modes within a single device markedly increased the HAR recognition accuracy from 51.4% to 81.4% owing to the integrated artificial vision system. The demonstration of an intelligent vision sensor offers a promising device platform for the development of highly efficient HAR systems and future smart optoelectronics. Highlights: 1 A novel GaN/AlN-based ultrathin quantum-disks-in-nanowires sensor was fabricated, demonstrating voltage bias tunable response characteristics to light stimuli. 2 Image enhancement functionality and a robust reservoir computing system were demonstrated based on the voltage tunable long-term and short-term persistent photocurrent respectively. 3 Furthermore, a high-performance artificial vision system with the two integrated functions was demonstrated, achieving a remarkable improvement in human action recognition.